Impact of Warmed Irrigation Fluid During Shoulder Arthroscopy on Patient Temperature, Recovery, and Cognitive Function: A Prospective Analysis of Influencing Factors - Jingfeng Liu; Xiaohong Huang; Xiaowei Xu; Yanyan Song; Jie Chen; Pei Yu; Tingjun Ye; Yin Zhang; Dahang Zhao; Gen Li; Lei Wang; Ying Wang; et al. (Orthopaedic Surgery, 2025)
ABSTRACT Objective To investigate the effects of warmed irrigation fluid during shoulder arthroscopy on patient temperature regulation, recovery outcomes, and cognitive function. Methods A randomized single‐blind prospective study (Level II) and a total of 85 patients who underwent shoulder arthroscopy at our hospital from February 2022 to April 2023 were selected, all of whom signed informed consent, which was randomly divided into two groups (warmed irrigation fluid group and room temperature fluid group). Among them, there were 29 males (34.1%) and 56 females (65.9%) (male:female ratio = 1:2), with an average age of 60.80 ± 11.70 years (ranging from 19 to 79 years). There were 50 patients (58.8%) aged over 60 and 35 patients (41.2%) aged under 60. All patients were diagnosed with rotator cuff injuries. We recorded primary patient data, anesthesia duration, anesthesia method, surgery duration, intraoperative temperature protection measures, irrigation volume, intraoperative nasopharyngeal and rectal temperatures, and preoperative and postoperative Mini‐Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) scores. Statistical analysis was performed to evaluate the impact of warmed irrigation fluid on patient temperature, recovery, and cognitive status. Results Analysis of the data from the 85 shoulder arthroscopy patients indicated that warming the irrigation fluid effectively prevented a decrease in core body temperature (nasopharyngeal and rectal temperatures), with significant differences observed at 120 min (nasopharyngeal temperature) and 105 min (rectal temperature). Patients with warmed irrigation fluid had a shorter average anesthesia recovery time than those without warming, although this difference was not statistically significant. Analysis of MMSE and MOCA scores revealed that the areas of cognitive decline post‐surgery mainly involved cumulative memory and attention, while orientation was not affected. Education level was identified as a factor influencing cognitive decline. Conclusion The administration of warmed irrigation fluid during shoulder arthroscopy has effectively preserved patients' core body temperature. This practice may contribute to a reduction in recovery time and complications associated with the procedure. Furthermore, minimally invasive techniques such as arthroscopy have been associated with a decreased incidence of postoperative cognitive impairment.